Does the Choice of Teaching Approach and ICT affect Teaching Quality During the Global COVID-19 Pandemic? A Case Study from Suranaree University of Technology - Phiakoksong, Somjin; Noimano, Sudarat; Pentamwa, Prapat (Asia Social Issues, 2022)
The global pandemic has disrupted conventional higher education that relies on in-person instruction. Online instruction has largely replaced in-person instruction in regions where COVID-19 restrictions are firm. This study investigates teaching pattern effectiveness and ICT use support at Suranaree University of Technology (SUT). The data were collected from 377 students and 217 teachers via online questionnaires. The Multivariate Analysis of Covariance (MANCOVA) and the Tukey-HSD method were able to identify significant trends in teaching approaches and ICT usage affecting both teaching and learning achievements. The results showed that effective teaching techniques included (1) Pre-recorded teaching videos as the main process at medium usage (average at 51.92% of teaching time) combined with (2) F2F live teaching and/or (3) Homework and assignments at low usage (average at 28.14% and 26.28% of teaching time, respectively). The ICT with significant impacts on teaching achievement were (1) ICT for communication i.e., Zoom Meeting and (2) ICT for classroom participation specifically Google forms. These teaching approaches and ICT usages patterns may support student were achievement and thus their learning during the global COVID-19 pandemic.